PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN INDUSTRI PENGHASIL BAHAN BAKU YANG TERDAFTAR DI BEI PERIODE 2011-2013 - Malinda Yuliani Pascarina; Raja Adri Satriawan Surya; Al Azhar A. ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study is applied Empirical Study for all industrial companies that produce raw materials listed in Indonesia Stock Exchange 2011-2013. The purpose of this study is to determine influence of Liquidity Ratio (Net Working Capital), Leverage Ratio (Debt to Asset Ratio), Activity Ratio (Total Asset Turnover), Profitability Ratio (Net Profit Margin and Gross Profit Margin) for profit growth. The data was employed in this study is secondary data from industrial companies that produce raw materials listed in Indonesia Stock Exchange during 2011-2013. Purposive sampling method is taken and generates 31 companies as sample. Statistical analysis which used in this study is multiple regression method by SPSS version 17.00. The study concluded that only three independent variables that have influence on profit growth they are Net Working Capital,Debt to Asset Ratio and Gross Profit Margin. While two other variables have no influence on profit growth they are Total Asset Turnover and Net Profit Margin. Based on the test result of the coefficient determination, the value of the Adjust R Square is 34.30% while the remaining 65.70% is influenced by other factors not included in this study.Keywords: Profit Growth, Financial Ratios, Industry and Raw Material